The combined influences of local heat application and resistance exercise on the acute mRNA response of skeletal muscle - McGlynn, Mark L.; Rosales, Alejandro M.; Collins, Christopher W.; Slivka, Dustin R. (Frontiers in Physiology, 2024)
The development and maintenance of skeletal muscle is crucial for the support of daily function. Heat, when applied locally, has shown substantial promise in the maintenance of muscle. The purpose was to determine the combined effects of local heat application and acute resistance exercise on gene expression associated with the human muscle growth program. Participants (n=12, 26±7 yr, 1.77±0.07 m, 79.6±15.4 kg, 16.1±11.6 %BF) completed an acute bilateral bout of resistance exercise consisting of leg press (11±2 reps, 170±37 kg) and leg extension (11±1 reps, 58±18 kg). Participants wore a thermal wrap containing circulating fluid (40°C, exercise + heat; EX+HT) during the entire experimental period and 4 h post-exercise, while the other leg served as an exercise-only (EX) control. Biopsies of the vastus lateralis were collected (Pre, Post, and 4hPost) for gene expression analyses. Intramuscular temperatures increased (Post, +2.2±0.7°C, p<0.001; 4hPost, +2.5±0.6°C, p<0.001) and were greater within the EX+HT leg post-exercise (+0.35±0.3°C, p=0.005) and after 4hPost (+2.1±0.8°C, p<0.001). MYOD1 mRNA was greater within the EX+HT leg vs. the EX (fold change=2.74±0.42, vs. 1.70±0.28, p=0.037). No other genes demonstrated temperature sensitivity between legs (p>0.05). mRNA associated with the negative regulator, myostatin (MSTN), decreased post-exercise (p=0.001) and after 4 h (p=0.001). mRNA associated with proteolysis decreased postexercise (FBXO32, p=0.001; FOXO3a, p=0.001) and after 4 h (FBXO32, p=0.001; FOXO3a, p=0.027). The elevated transcription of the myogenic differentiating factor 1 (MYOD1) after exercise in the heated condition may provide a mechanism by which muscle growth could be enhanced.